Notification of suspicion on the web page of the General Prosecutor’s Office and in the newspaper “Uryadovyi Kurier”: requirements and algorithm of publication - A. V. Hutnyk (Bulletin of Kharkiv National University of Internal Affairs)
The study is aimed at analysing the legal acts establishing the procedure for publishing notices of suspicion on the website of the Prosecutor General’s Office and in the newspaper “Uryadovyi Kurier” and notices of suspicion already published in these sources, determining the requirements for them and developing an algorithm for publication for prosecutors and investigators. The author uses the methods of analysis and synthesis, induction and deduction, comparative legal, formal and logical, systemic and structural, graphical and other methods of scientific research.